Advanced Methodology for Emulating Local Operating Conditions in Proton Exchange Membrane Fuel Cells - Marine Cornet; Arnaud Morin; Jean-Philippe Poirot-Crouvezier; Yann Bultel (Data)
This work focuses on the study of operating heterogeneities on a large MEA’s active surface area in a PEMFC stack. An advanced methodology is developed, aiming at the prediction of local operating conditions such as temperature, relative humidity and species concentration. A physics-based Pseudo-3D model developed under COMSOL Multiphysics allows for the observation of heterogeneities over the entire active surface area. Once predicted, these local operating conditions are experimentally emulated, thanks to a differential cell, to provide the local polarization curves and electrochemical impedance spectra. Coupling simulation and experimental, thirty-seven local operating conditions are emulated to examine the degree of correlation between local operating conditions and PEMFC cell performances. Researchers and engineers can use the polarization curves and Electrochemical Impedance Spectroscopy diagrams to fit the variables of an empirical model or to validate the results of a theoretical model.